Enterococcus faecalis leakage of root canal sealers: An ex vivo study - D'Ercole, S.; Filippakos, A.; De Toledo Leonardo, R. [UNESP]; Pameijer, C. H.; Tripodi, Domenico (My University, 2012)
The aim of this ex vivo study was to evaluate bacterial penetration after filling root canals using 3 different techniques. Three experimental groups of 25 teeth each, obturated with lateral-warm-vertical condensation of gutta-percha, Microseal technique and EndoREZ® system, respectively, were tested in a split chamber model system using Enterococcus faecalis and monitored for 180 days to determine bacterial penetration. A statistical analysis was performed using the Kaplan-Meier method. Median survival time was 25 days for Microseal system, 41 for lateral-warm-vertical condensation and 81 for EndoREZ®. Significant differences were demonstrated between Microseal and EndoREZ® (p<0.001) and between Microseal and lateral-warm-vertical condensation technique (p<0.05). No statistically significant differences were observed between EndoREZ® and lateral-warm-vertical condensation. After 180 days of assessment, 20% of the EndoREZ® samples resisted bacterial penetration and furthermore, the EndoREZ® system has the potential to be a filler system compatible with other currently used systems. Copyright © by BIOLIFE, s.a.s.
Keywords: Bacteria; Biocompatibility; Filling method; Gutta-percha; Leakage; Resin sealer